What works to control COVID-19? Econometric analysis of a cross-country panel - Liming Chen; David Raitzer; Rana Hasan; Rouselle Lavado; Orlee Velarde (Asian Development Bank (ADB), 2020)
We use cross-country panel data to examine the effects of a variety of nonpharmaceutical interventions used by governments to suppress the spread of coronavirus disease (COVID-19). We find that while lockdown measures lead to reductions in disease transmission rates as captured by the reproduction number, Rt, gathering bans appear to be more effective than workplace and school closures, both of which are associated with large declines in gross domestic product. Further, our estimates suggest that stay-at-home orders are less effective in countries with larger family size and in developing economies. We also find that incentives are very important, as efforts at ramping up testing and tracing COVID-19 cases are more effective in controlling the spread of disease in countries with greater coverage of paid sick leave benefits. As future waves of the disease emerge, the use of more targeted and better incentivized measures can help keep the epidemic controlled at lower economic cost.
Keywords: I10; I18; O40; 330; COVID-19; cross-country data; economic impact; nonpharmaceutical interventions